Hubungan Antara Manajemen Konflik dalam Kelompok Belajar dengan Kerja Sama Tim Mahasiswa S1 Ilmu Keperawatan Universitas Islam Sultan Agung Semarang - Farah Nura Ini; Retno Issroviatiningrum; Muh. Abdurrouf (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Conflict management is the ability of individuals or groups to handle differences of opinion and tension. Teamwork is an essential skill for nursing students, as the success of group tasks depends largely on communication, collaboration, and the ability to resolve conflicts that arise during the learning process. This study aims to analyze the relationship between conflict management in study groups and teamwork among nursing students. This study employs a cross-sectional technique and is quantitative in nature. There were 105 participants in this study The sample selection method using simple random sampling, namely random sampling, was used in this research. Data were analyzed using the Spearman rank test, utilizing a Likert scale consisting of 14 statements for the conflict management variable and 20 statements for the teamwork variable. With 60 respondents (57.1%), the majority of the outcomes from conflict management fall into the high category, according to the research that has been completed. With 59 responders (51.4%), teamwork is primarily rated as high. The p-value of 0.000 (<0.05) obtained from the statistical test indicates a relationship between the management of conflict in study groups and teamwork among undergraduate Nursing students at Sultan Agung Islamic University, Semarang.